Nursing outcomes for pain assessment of patients undergoing palliative care - Bruna Schroeder Mello; Miriam de Abreu Almeida; Lisiane Pruinelli; Amália de Fátima Lucena
ABSTRACT Objective: To select outcomes and indicators of the Nursing Outcomes Classification (NOC), in order to assess patients with cancer under palliative care with Acute and Chronic Pain Nursing Diagnoses; and to construct the conceptual and operational definitions of the indicators. Method: Expert opinion study and literature review. The sample consisted of 13 experts. The data collection was in own tool applied in face-to-face meeting and by e-mail. In the analysis of the data, it was considered between 75% and 100% of agreement. Results: Eight outcomes and 19 indicators were selected. The results with higher scores were Pain Level, Pain Control and Client Satisfaction: Pain Management. For all indicators selected, conceptual and operational definitions were constructed. Conclusion: The selection of results and priority indicators for the assessment of pain in palliative care, as well as the construction of its definitions, will support clinical practice.